Role of normobaric oxygen treatment on newborn hypoxia-ischemia - Keleştemur, Taha; Beker, Mustafa Çağlar; Çağlayan, Ahmet Burak; Yalçın, Esra; Altunay, Serdar; Dalay, Arman; Sertel, Elif; Dilden, Aysun; Çağlayan, Berrak; Kılıç, Ertuğrul (Wiley-Blackwell, 2016)
[Abstract Not Available]
Keywords: Normobaric Oxygen; Treatment; Hypoxia-Ischemia